2019
DOI: 10.1590/0037-8682-0249-2018
|View full text |Cite
|
Sign up to set email alerts
|

Viral etiology of acute respiratory infections in children in Southern Iran

Abstract: Introduction: Prevalence of influenza A virus (Flu-A), respiratory syncytial virus (RSV), and human metapneumovirus (hMPV) was assessed in children with acute respiratory infections (ARIs). Methods: Nasopharyngeal aspirates and throat swabs were subjected to real-time polymerase chain reaction (PCR) to detect RSV and Flu-A and to conventional PCR to detect hMPV. Results: Of the 156 children assessed, 93 (59.6%) carried at least one virus, with 35.9% positive for RSV, 14.1% for hMPV, and 9.6% for Flu-A. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
2
5
1
Order By: Relevance
“…As an important find, we had a high rate of RV/EV isolation, there is growing evidence that supports that this pathogen can contribute to significant respiratory disease and could be associated with morbidity, admission to the PICU, or need of mechanical ventilation ( 42 , 43 ). Unlike other studies, as a prospective study conducted in Madagascar that reports human metapneumovirus (HMPV) infection in about 14% of children with ARF, we didńt have any isolation of HMPV ( 39 ), but we found another type of coronavirus as NL63 and HKU1 in a low-rate proportion, demonstrating the diversity of acute respiratory infections pathogens and the variations in the viral circulation for each region. The viral isolation behavior was different between age groups, being higher in children under 5 years of age, mainly in infants (<2 years).…”
Section: Discussioncontrasting
confidence: 99%
“…As an important find, we had a high rate of RV/EV isolation, there is growing evidence that supports that this pathogen can contribute to significant respiratory disease and could be associated with morbidity, admission to the PICU, or need of mechanical ventilation ( 42 , 43 ). Unlike other studies, as a prospective study conducted in Madagascar that reports human metapneumovirus (HMPV) infection in about 14% of children with ARF, we didńt have any isolation of HMPV ( 39 ), but we found another type of coronavirus as NL63 and HKU1 in a low-rate proportion, demonstrating the diversity of acute respiratory infections pathogens and the variations in the viral circulation for each region. The viral isolation behavior was different between age groups, being higher in children under 5 years of age, mainly in infants (<2 years).…”
Section: Discussioncontrasting
confidence: 99%
“…Males were more represented in our patients group (53 males and 31 females). Masculine gender predominance was also reported in other studies [12,13]. Basing on case investigation forms, several clinical signs were detected.…”
Section: Discussionsupporting
confidence: 79%
“…Our results agree with other investigations about all age groups from numerous countries. For instance, positive ARIs pathogens were reported in 65.1% of patients in Cameroon [10], in 65% of patients in north of Morocco [7], 61.6% in Sweden [16], and 59.6% in Iran [13]. Relatively lower rates of positive cases were reported in Italy with 41.7% [17], and in Peru (42.6%) [18].…”
Section: Discussionmentioning
confidence: 96%
“…We found that 78% out of the 33,404 ILIs cases tested positive for at least one respiratory pathogen. Many other similar studies reported lower percentages, including Saudi Arabia (24% of 4611), Iran (59.6% of 156), Cameroon (65% of 365), and Philippines (43% of 1864) (Albogami et al, 2018;Njouom et al, 2012;Halaji et al, 2019;Otomaru et al, 2015). On the other hand, and in accordance with our current findings, a report on respiratory viruses among children (6 months-10 years) in eight countries (Australia, South East Asia, and Latin America) indicated a positivity rate of 79.6% (Taylor et al, 2017).…”
Section: Discussionmentioning
confidence: 90%